PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada CV. XP Computer, Boyolali) - dewi, fitriana; puji rahayu, listyowati; safitri, Unna (Universitas Boyolali, 2020)
Based on the results of the study note that the price of a partial no effect on purchasing decisions this is evidenced by the value of t count < t table it’s about -0.2243 <1.984. As for the quality of service is known that the partial effect on purchasing decisions. This is evidenced in the grain of service quality regarding the reliability and assurance that the value of tcount > ttable 3.986> 1.984 and 2.011> 1.984. Determination test result there is influence between price and quality of service to decision of purchase equal to 38% whereas 62% influenced by other factor not examined in this research. Keywords: Price, Service Quality, Purchase Decision